Light colors and comfortable warmth: Crossmodal correspondences between thermal sensations and color lightness influence consumer behavior. (March 2019) - Motoki, Kosuke; Saito, Toshiki; Nouchi, Rui; Kawashima, Ryuta; Sugiura, Motoaki
Highlights: Warmth and light colors were matched. Warmth increased visual attention directed toward light-colored goods. Warmth increased consumer preferences for light-colored goods under conditions of comfortable (but not uncomfortable) warmth. Abstract: Consumers are often surrounded by somatosensory (e.g., warmth) and visual (e.g., color) information. For example, consumers often see light-colored goods under warm conditions. Previous studies have shown that sensory interactions, such as those involving auditory and visual stimuli, influence consumer behaviors. However, it remains unknown whether somatosensory–visual information (e.g., warmth and color lightness) interactively guide consumer behaviors. Additionally, the conditions under which sensory interactions increase consumer preferences are also unclear. This study focused on how the effects of the novel correspondences between somatosensory and visual (warmth and color lightness) perceptions extend from the capture of visual attention to the formation of preferences, as well as on how attitudes toward sensory experiences (i.e., positive reactions to sensory experiences) play critical roles in preference formation. The results showed the existence of crossmodal correspondences between feeling warm and light colors (Study 1), and such crossmodal correspondences influenced consumers' visual attention. Physical warmth increased the visual attention directed toward light-colored goods (Study 2). Although this correspondence did not directly influence consumer preferences (Study 3), it did increase consumer preferences for light-colored goods under conditions of comfortable (but not uncomfortable) warmth (Study 4). These results reveal novel crossmodal correspondences between thermal sensations and levels of color lightness and demonstrate how such correspondences have consumer-relevant consequences.